Low Serum Vitamin D Is Not Correlated With Myopia in Chinese Children and Adolescents - Li, Xiaoman; Lin, Haishuang; Jiang, Longfei; Chen, Xin; Chen, Jie; Lu, Fan (Frontiers in Medicine, 2022)
Purpose: This cross-sectional study investigated the association between serum 25-hydroxyvitamin D [25(OH)D] concentration and myopia in two groups of Chinese children aged 6-14 years from different geographic and economic locations. Methods: A total of 294 children from a lowland area and 89 from a highland area were enrolled as two groups of study subjects. The visual acuity, ocular biometry and automated refraction were measured. The serum level of 25(OH)D was determined by chemiluminescence immunoassay. Near vision and outdoor exposure durations were assessed with a questionnaire interview. Data were analyzed for differences using Chi-square and Wilcoxon rank sum tests. The risk factors were evaluated using logistic regression analysis. Results: We found that the serum level of 25(OH)D of the subjects from lowland area was 20.9ng/mL which was higher than that of subjects from highland area (16.9ng/mL). The median spherical equivalent refraction (SER) was -0.25 diopters(D) in lowland subjects and -0.63D in highland subjects. The prevalence of myopia was 45.2% in lowland subjects and 55.1% in highland subjects. The average axial length was similar, 23.6 mm and 23.1 mm in lowland and highland subjects, respectively. We found no statistical difference between the average SER and serum 25(OH)D concentration in subjects of either lowland or highland area. The ratio of myopia to non-myopia was also similar in subjects with three levels (sufficient, deficient and insufficient) of serum 25(OH)D in these two areas. Conclusions: There is no association between serum 25(OH)D concentration and myopia in the 6-14 years old Chinese children.